Epithelio--mesenchymal interactions are critical for Quox 7 expression and membrane bone differentiation in the neural crest derived mandibular mesenchyme. - Takahashi, Y (1991)
In higher vertebrates, branchial arch mesenchyme (ectomesenchyme) is derived from the cephalic neural crest. The ectomesenchyme of the mandibular arch yields the Meckel's cartilage and several membrane bones. We previously reported the isolation of a quail homeobox gene, Quox 7. In common with its mouse counterpart Hox 7, Quox 7 is highly expressed in the medioventral part of the mandibular arch and later in the precursor cells of the membrane bones. Since bone differentiation from ectomesenchyme is strictly dependent upon a signal provided by the mandibular epithelium, we decided to see whether the regulation of Quox 7 gene activity might be correlated with epithelio--mesenchymal interactions. Quox 7 expression was studied in E3 mandibular ectomesenchyme cultured in vitro or grafted on the chick chorioallantoic membrane either alone or recombined with the homotopic and heterotopic epithelia. We found that Quox 7 mRNA was undetectable after 48 h in cultures of mesenchyme alone while it remained abundant in non-cartilaginous tissue of the mandibular arch ectomesenchyme recombined with its own epithelium. The signal provided by the mandibular epithelium for Quox 7 expression can also arise from various heterotopic epithelia, e.g. of dorsal or ventral body wall and of limb bud. Thus the effect of the epithelium on Quox 7 expression in mesenchymal cells strictly parallels that on bone formation. These results strongly suggest that the epithelio-mesenchymal interactions have an essential role on the regulation of Quox 7 gene, the product of which seems to be, in turn, necessary for the execution of the skeletal developmental program in the facial area.